NONSMOKERS GROUP ASKS BREATHING ROOM - EISNACH, DWIGHT (Tufts Archival Research Center, 2007)
Illegible/Difficult to Read; Article in the Duluth, Minnesota Harold reporting on the Association For Non Smokers Rights. States that Association’s mission is to segregate smokers from non smokers in public places. Mentions Association’s recent actions taken to promote smoking segregation in restaurants.